حساب الجوائز البيتونية العميقة باستخدام نموذج جائز شبكي - اندراوس, غصون ميشال (Latakia University Journal -Engineering Sciences Series, 2014)
تُعَدُّ الجوائز العميقة من العناصر الإنشائية المهمة, التي نصادفها في بعض المنشآت كجدران الصوامع والخزانات، والجوائز القصيرة المجاز، والجوائز الحاملة للرافعات وأساسات الآلات ولغيرها من المنشآت الخاصة. حيث كان يتم حساب هذه الجوائز وتصميمها بطرق مبسطة تعتمد على علاقات حساب تقريبية لا تأخذ بعين الاعتبار السلوك الفعلي لهذه الجوائز. يهدف البحث إلى دراسة سلوك الجوائز العميقة، وتوزع الإجهادات الداخلية فيها، وذلك باستخدام نموذج جائز شبكي، حيث يعتمد هذا النموذج على تمثيل الأجزاء المضغوطة من الجائز العميق بعناصر ضغط والأجزاء المشدودة منه بعناصر شد، أي تمثيل الجائز العميق بجائز شبكي مكافئ مؤلف من عناصر ضغط وعناصر شد، وذلك حسب توضع الأحمال عليه من أجل الوصول إلى الحل الأمثل الذي يحاكي السلوك الفعلي اللاخطي لهذه الجوائز. The deep concrete beams are an important structural members, which we can see in some of structures as: the walls of tanks, hermitages, beams with short spans, girders of cranes, foundations of machines, and some of special structures. The design of these beams was depending on an approximate methods, regardless of the actual behavior for that beams. The aim of this research is, to study the actual behavior of deep beams, and distribution of stresses, which differs from normal beams partly. We will use the strut-and-tie model, which offers: compressive parts of deep beam are equivalent to compression members, and tensile parts are equivalent to tension members, so the deep beam will be equivalent to a truss beam with compression and tension members, with different cases of loading, in order to obtain the optimum analysis of the actual nonlinear behavior of deep beams.